Epidemiological trends of imported infectious diseases in Japan: Analysis of imported 2-year infectious disease registry data. Issue 4 (April 2021) - Kutsuna, Satoshi; Asai, Yusuke; Yamamoto, Kei; Shirano, Michinori; Konishi, Keiji; Asaoka, Tomohiro; Yamato, Masaya; Katsuragi, Yukiko; Yamamoto, Yudai; Sahara, Toshinori; Tamiya, Aya; Nakamura-Uchiyama, Fukumi; et al.
Abstract: Introduction: The epidemiology of infectious diseases in Japan remains undefined despite the increasing tourism. GeoSentinel, an epidemiological surveillance system for reporting imported infectious diseases, has only two participating facilities in Japan. Although the number of infectious diseases is reported by the National Institute of Infectious Diseases, there is no detailed clinical information about these cases. Therefore, we established J-RIDA (Japan Registry for Infectious Diseases from Abroad) to clarify the status of imported infectious diseases in Japan and provide detailed information. Methods: J-RIDA was started as a registry of imported infectious diseases. Case registration began in October 2017. Between October 2017 and September 2019, 15 medical institutions participated in this clinical study. The registry collected information about the patient's age, sex, nationality, chief complaint, consultation date, date of onset, whether visit was made to a travel clinic before travel, blood test results (if samples were collected), travel history, and final diagnosis. Results: Of the 3046 cases included in this study, 46.7% to Southeast Asia, 13.0% to Africa, 13.7% to East Asia, 11.5% to South Asia, 7.5% to Europe, 3.8% to Central and South America, 4.6% to North America, 3.9% to Oceania, and 2.8% to Central and west Asia. More than 85% of chief complaints were fever and general symptoms, gastrointestinal symptoms, respiratory symptoms, or dermatologic problems. The most common diseases were travelers' diarrhea, animal bite, upper respiratory infection, influenza, and dengue fever. Conclusions: We summarized two-year cases registered in Japan's imported infectious disease registry. These results will significantly contribute to the epidemiology in Japan.